Light up your life discover your true purpose and potential - Cooper, Diana (Judy Piatkus, 1991)
This book aims to show how to learn to understand the spiritual laws of the universe and apply them to everyday life. The author shows how we can claim spiritual power and use it to create good relationships, prosperity and success.